CITRA WANITA DALAM NOVEL âIMROâAH INDA NUQTHAH ASH-SHIFRâ (PEREMPUAN DI TITIK NOL) KARYA NAWAL EL-SAâDAWIAhmad HamzahPascasarjana Universitas Negeri Surabaya hamzah.um@gmail.com (Lentera, Jurnal Studi Perempuan, 2014)
Abstract:  The  novel  written  by  Nawal  El-Sa’dawi  entitled  Imro’ah  inda  Nuqthah Ash-Sifr which then translated to Indonesia as Perempuan di Titik Nol is a novel that portrays women controversially. Feminist theories will be used to analyze the novel. Here, the women are described psychologically and socially. In psychological point of view, woman described as a smart and brainy person; one who loves to learn, to be loved and loving. A woman who wants the freedom, changing her life to the better one,  someone  who  does  not  need  a  protector,  a  woman  who  has  dignity,  brave, confident, dependent and hard working. While from social point of view, a woman is described as a wife, a mother, a worker, a doctor, a prostitute, a teacher, a pimp. Woman cannot be a leader, she does not deserve to get the same education as man. Woman always becomes the second in the workplace. She is the other. Keywords: psychological, brave, confident, social, second position, discrimination.